Analisis Perhitungan Harga Pokok Produksi dengan Metode Full costing dalam Menetapkan Harga Jual pada UMKM Jus Buah N2N: Analysis of the Calculation of the Cost of Production with the Full Costing Method in Setting the Selling Price for MSMEs of N2N Fruit Juice - Siti Nazwa Rahmah; Nazwa Namira Adnan; Cantika Deani Azzahra; Eka Diah Ciptorini; Lintang Khoirunnisa (PT Cakrawarti Empat Proksi, 2026)
This research analyzes the calculation of the Cost of Goods Manufactured (COGM) using the full costing method at UMKM Jus Buah N2N, a micro, small, and medium enterprise operating in the beverage sector. The background of this study relates to the need for accurate production cost calculations to determine product cost prices and support business sustainability. In daily practice, MSME owners often do not fully calculate all elements of production costs, which can lead to errors in business cost management. The purpose of this study is to identify and calculate all components of production costs, including raw material costs, direct labor costs, and factory overhead costs, by applying the full costing method. The method used in this research is descriptive qualitative, with data collection conducted through interviews, observation, and documentation. The research findings show that the total production cost at UMKM Jus Buah N2N reached IDR 11,925,000, where this calculation uses the full costing method. Of this total, raw material costs amounted to IDR 6,175,000, direct labor costs were IDR 4,500,000, and factory overhead costs were IDR 1,250,000. With a total production of 870 portions, the Cost of Goods Manufactured obtained was IDR 13,706 per portion. The application of the full costing method can assist MSMEs in calculating production costs in a more comprehensive, accurate, and systematic manner, thereby contributing to better business decision-making.